Классификация нелокальных краевых задач в узкой полосе - Борок, В.М.; Кенне, Э. (Український математичний журнал, 1994)
For the general linear partial differential equation with constant coefficients, a criterion of correctness is established for a boundary-value problem on the strip ΠY=R×[0,Y]with an integral in the boundary condition. A complete classification of such problems is obtained dependently on their asymptotic properties as Y→0.